Keeping Africanized Honey Bees Out of Wildlife Nest Boxes - William H. Kern, Jr. (EDIS)
ENY-838, a 4-page illustrated fact sheet by William H. Kern, Jr., provides useful information for keeping pests out of bird and mammal nest boxes, especially the Africanized honey bee, which has become established in Florida, and sets up colonies in smaller and lower locations which may displace wildlife that uses these locations as dens. Includes recommendations, what to do if bees have invaded your nest box, and references. Published by the UF Department of Entomology and Nematology, January 2007.